Priming‐induced alterations in histone modifications modulate transcriptional responses in soybean under salt stress. (27th January 2022) - Yung, Wai‐Shing; Wang, Qianwen; Huang, Mingkun; Wong, Fuk‐Ling; Liu, Ailin; Ng, Ming‐Sin; Li, Kwan‐Pok; Sze, Ching‐Ching; Li, Man‐Wah; Lam, Hon‐Ming
SUMMARY: Plants that have experienced certain abiotic stress may gain tolerance to a similar stress in subsequent exposure. This phenomenon, called priming, was observed here in soybean ( Glycine max ) seedlings exposed to salt stress. Time‐course transcriptomic profiles revealed distinctively different transcriptional responses in the primed seedlings from those in the non‐primed seedlings under high salinity stress, indicating a stress response strategy of repressing unhelpful biotic stress responses and focusing on the promotion of those responses important for salt tolerance. To identify histone marks altered by the priming salinity treatment, a genome‐wide profiling of histone 3 lysine 4 dimethylation (H3K4me2), H3K4me3, and histone 3 lysine 9 acetylation (H3K9ac) was performed. Our integrative analyses revealed that priming induced drastic alterations in these histone marks, which coordinately modified the stress response, ion homeostasis, and cell wall modification. Furthermore, transcriptional network analyses unveiled epigenetically modified networks which mediate the strategic downregulation of defense responses. Altering the histone acetylation status using a chemical inhibitor could elicit the priming‐like transcriptional responses in non‐primed seedlings, confirming the importance of histone marks in forming the priming response. Significance Statement: Understanding how plants adapt to stress conditions is important for developing strategies for crop improvement. In this study, a mild salt treatment of soybean ( Glycine max ) seedlings primed them for a more effective response against subsequent high salinity stress, by altering the genome‐wide distribution of histone marks to upregulate osmotic stress response genes and downregulate those for defense responses.